Men and welfare - Ladlow, Linzi; Way, Laura; Tarrant, Anna (Research officer) (Routledge research in gender and society, 2023)
This book explores the complex, evolving relationships between men, masculinities and social welfare in contemporary context. It is inspired by themes examined in 'Men, Gender Divisions and Welfare', an edited collection published in 1998 by Popay, Hearn and Edwards. While international policy agendas reflect a growing commitment to critically addressing the relations between men, masculinities and policy, in policy and popular discussions, societies continue to grapple with the question of 'what to do with men?'. This question reflects an ongoing tension between the persistence of men's power and control over welfare and policy development, alongside their ostensible avoidance of welfare services. The collection constitutes an up-to date account of the gendered and social implications of policy and practice change for men, as well as their inherent contradictions and complexities, tracing both stability and change over the past twenty-five years. This book will appeal to students and scholars in diverse fields, particularly in sociology, social policy, applied social sciences, gerontology, gender studies, youth studies, welfare studies, politics, and social geography. Given the volume's empirical attention throughout to both policies and practice developments, it will also be of interest to those training in applied and vocational degrees such as health and social care, social work, family support, and health visiting"--